1995
DOI: 10.1073/pnas.92.7.2924
|View full text |Cite
|
Sign up to set email alerts
|

Defective G protein activation of the cAMP pathway in rat kidney during genetic hypertension.

Abstract: The Rats developing genetic hypertension, such as the OkamotoAoki strain of spontaneously hypertensive rat (SHR), provide opportunities for insight into mechanisms involved in the pathogenesis of essential hypertension in humans. Crosstransplantation studies indicate that the kidneys play a pivotal role in the development of hypertension in genetically hypertensive rats (1-3). Alterations in renal vascular resistance, glomerular filtration rate, renal blood flow, and sodium and water retention have been descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 25 publications
4
47
0
1
Order By: Relevance
“…The enhanced renal sensitivity to Ang II in SHR is in part due to defects in the G s (Chatziantoniou et al, 1995) and G i (Jackson, 1994;Gao et al, 2003) signal transduction pathways but apparently is independent of changes in the number of angiotensin receptors (Gao et al, 2003). The findings of the present study strongly suggest that enhanced renal sensitivity to Ang II in SHR is also independent of renal degradation of Ang II.…”
Section: Discussionsupporting
confidence: 66%
“…The enhanced renal sensitivity to Ang II in SHR is in part due to defects in the G s (Chatziantoniou et al, 1995) and G i (Jackson, 1994;Gao et al, 2003) signal transduction pathways but apparently is independent of changes in the number of angiotensin receptors (Gao et al, 2003). The findings of the present study strongly suggest that enhanced renal sensitivity to Ang II in SHR is also independent of renal degradation of Ang II.…”
Section: Discussionsupporting
confidence: 66%
“…However, fenoldopam has been reported to fail to vasodilate the kidney of some patients with essential hypertension (43). The ability of fenoldopam to counteract the renal vasoconstrictor effect of exogenous angiotensin II and inhibit tubuloglomerular feedback is also impaired in the SHR (44,45). It is possible that differences in published reports may be related to differences in classes of hypertension being studied (salt-sensitive vs. saltresistant) or different experimental conditions (basal tone vs. basal, ANOVA on ranks, Dunnet's test; ϩ, P Ͻ 0.05 vs. basal, t test; #, P Ͻ 0.05 GRK4␥ A142V vs. WT (wild-type).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies (4,14,31) have indicated that impaired coupling between membrane receptors and downstream signal transduction events also occurs in spontaneously hypertensive rats. The present study is the first to demonstrate that a high-salt diet alone can lead to impaired coupling between membrane receptors and downstream messenger systems.…”
Section: Effect Of High-salt Diet On Electrical and Mechanical Responmentioning
confidence: 99%